Concordance between the delirium motor subtyping scale (DMSS) and the abbreviated version (DMSS-4) over longitudinal assessment in elderly medical inpatients. (26th November 2015) - Fitzgerald, James; O'Regan, Niamh; Adamis, Dimitrios; Timmons, Suzanne; Dunne, Colum; Trzepacz, Paula; Meagher, David
ABSTRACT: Background: Delirium is a common neuropsychiatric syndrome that includes clinical subtypes identified by the Delirium Motor Subtyping Scale (DMSS). We explored the concordance between the DMSS and an abbreviated 4-item version in elderly medical inpatients. Methods: Elderly general medical admissions ( n = 145) were assessed for delirium using the Revised Delirium Rating scale (DRS-R98). Clinical subtype was assessed with the DMSS (which includes the four items included in the DMSS-4). Motor subtypes were generated for all patient assessments using both versions of the scale. The concordance of the original and abbreviated DMSS was examined. Results: The agreement between the DMSS and DMSS-4 was high, both at initial and subsequent assessments ( κ range 0.75–0.91). Intraclass Correlation Coefficient (ICC) for all three raters for the DMSS was high (0.70) and for DMSS-4 was moderate (0.59). Analysis of the agreement between raters for individual DMSS items found higher concordance in respect of hypoactive features compared to hyperactive. Conclusions: The DMSS-4 allows for rapid assessment of clinical subtype in delirium and has high concordance with the longer and well-validated DMSS, including over longitudinal assessment. There is good inter-rater reliability between medical and nursing staff. More consistent clinical subtyping can facilitate better delirium management and more focused research effort.